2005
DOI: 10.1111/j.1365-294x.2005.02473.x
|View full text |Cite
|
Sign up to set email alerts
|

Coyote movements and social structure along a cryptic population genetic subdivision

Abstract: A recent region-wide study determined that the central California coyote ( Canis latrans ) population was genetically subdivided according to habitat bioregions, supporting the hypothesis that coyotes exhibit a dispersal bias toward their natal habitat type. Here, we further investigated this hypothesis using radio-collared coyotes captured on a 150-km 2 study site on the border of (i.e. overlapping) two bioregions (Great Valley and Cascade Mountains). As predicted, most coyotes were assigned (based on a prior… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
68
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(72 citation statements)
references
References 33 publications
3
68
1
Order By: Relevance
“…When the results of the current study are added to those of previous studies on this topic (Haughland & Larsen 2004;Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006;Selonen et al 2007), evidence is accumulating that natal experience may play an important role in determining habitat choice for freeliving dispersers in natural landscapes. In light of this evidence, it seems likely that NHPI may impact ecological and evolutionary processes in a variety of species under natural conditions.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…When the results of the current study are added to those of previous studies on this topic (Haughland & Larsen 2004;Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006;Selonen et al 2007), evidence is accumulating that natal experience may play an important role in determining habitat choice for freeliving dispersers in natural landscapes. In light of this evidence, it seems likely that NHPI may impact ecological and evolutionary processes in a variety of species under natural conditions.…”
Section: Resultsmentioning
confidence: 99%
“…Despite the considerable interest in the broader implications of NHPI, the vast majority of empirical studies of this phenomenon have been conducted in the laboratory and used insects as the experimental subjects (Davis & Stamps 2004;Davis 2006;Stamps & Davis 2006), although a few field studies have reported a population genetic structure consistent with NHPI (Sacks et al 2005;Tonnis et al 2005;Pilot et al 2006). Recently, Haughland & Larsen (2004) found that red squirrels (Tamiasciurus hudsonicus) born in either logged or intact coniferous forests were likely to recruit to new sites that were structurally similar to their natal site.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, Pilot et al (2006) found that genetic differentiation in European wolves was correlated with climate, habitat types, and diet composition and also suggested that natalhabitat biased dispersal was the underlying mechanism linking population ecology vntin genetic sb:xicture. Apparently, in large canids, ecotypic divergence may be the primary mode of differentiation (Carmichael et al 2001;Musiani 2003;Geffen et al 2004;Sacks et al 2004Sacks et al , 2005Pilot et al 2006;Carmichael et al in press) presenting an alternative to topographically induced population structure (Avise 2000).…”
Section: Prey-mediated Differentiation Of Tundra/taiga and Boreal Conmentioning
confidence: 99%
“…To test for differences in population membership values (q) among runs, i.e. the posterior probability of an individual originating from the same population where it was sampled, we used a non-parametric Kruskal-Wallis test in R (Sacks et al 2005). …”
Section: Population Structurementioning
confidence: 99%